2014
DOI: 10.1007/s10482-014-0146-z
|View full text |Cite
|
Sign up to set email alerts
|

Variibacter gotjawalensis gen. nov., sp. nov., isolated from soil of a lava forest

Abstract: A novel bacterial strain designated GJW-30(T) was isolated from soil of the lava forest, Gotjawal, located in Aewol, Jeju, Korea. Strain GJW-30(T) was found to be strictly aerobic, Gram-negative and to form pleomorphic, non-motile rods and white colonies on R2A agar. The major fatty acids were identified as C18:1ω7c, C16:0 and C17:0, the predominant isoprenoid quinone as Q-10, the polar lipids as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylcholine, an unidentified aminol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…At present, some areas of the Gotjawal are protected, but about 50% of the original forests have been replaced by secondary growth due to losses from deforestation, agricultural land use, and urbanization[ 3 ]. Gotjawal soils are considered highly fertile due to their high organic matter and low mineral content, but relatively little is known about their microbiology[ 2 , 4 ]. Previous cultivation-based studies of these soils have identified several new genera and species [ 2 , 4 8 ], but more comprehensive analyses are needed to understand patterns of microbial community structure and function, and interactions with Gotjawal plant assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some areas of the Gotjawal are protected, but about 50% of the original forests have been replaced by secondary growth due to losses from deforestation, agricultural land use, and urbanization[ 3 ]. Gotjawal soils are considered highly fertile due to their high organic matter and low mineral content, but relatively little is known about their microbiology[ 2 , 4 ]. Previous cultivation-based studies of these soils have identified several new genera and species [ 2 , 4 8 ], but more comprehensive analyses are needed to understand patterns of microbial community structure and function, and interactions with Gotjawal plant assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…nov., isolated from the soil of Aewol Gotjawal forest, one of four Gotjawal sites on Jeju Island (Kim et al. ); this isolate belongs to α ‐ Proteobacteria and shows high similarity with Bradyrhizobium oligotrophicum LMG 10732 (93.6%).…”
Section: Resultsmentioning
confidence: 99%
“…Bosea is a genus of bacteria in the bradyrhizobiaceae family, which has the ability to remove and degrade the pollutants arsenic, antinomy, and ciprofloxacin (Lu et al, 2018; Zhang et al, 2018). The genus Variibacter was first proposed by Kim et al (2014). One of its members, V. gotjawalensis GJW-30 T , was sequenced by Lee et al (2016), who found that various genes of strain GJW-30 T encode functional enzymes for nitrate reduction, ginsenoside biosynthesis and degradation, and gibberellin biosynthesis and inactivation.…”
Section: Discussionmentioning
confidence: 99%